A low cost and high efficient Ba9(Lu2-x-yAlx)Si6O24:yCe3+ cyan-emitting phosphor. Issue 8 (1st June 2020) - Wang, Lei; Yuan, Chenxu; Hu, Pan; Li, Ruiyang; Liu, Yongfu; Sun, Peng; Dong, Rui; Qi, Xiaopeng; Jiang, Jun; Jiang, Haochuan
Abstract: White LEDs constructed by near-ultraviolet chips and red/green/blue/cyan-emitting phosphors are an important route for healthy lighting. However, efficient cyan-emitting phosphors are quite scarcity. The cyan-emitting phosphor Ba9 Lu1.5 Al0.5 Si6 O24 :Ce 3+ (BLASO:Ce 3+ ) was reported for the first time. Under 400 nm excitation, BLASO:Ce 3+ shows a emission peak at 488 nm with an FWHM of about 117 nm. At room temperature, the internal quantum efficiency (IQE) can reach as high as 90.8%. At 150 °C, the IQE decreases to 81.5%, indicating an excellent thermal stability. The effect of the Al substitution for Lu on crystal structures and photoluminescence were investigated. The homogeneity of the luminescence was diagnosed by viewing microscopic particles based on the scanning electron microscope (SEM) equipped a cathodoluminescence (CL) system.